A Defense of the Dead Donor Rule - Magnus, David (The Hastings Center report, 2018)
Discussion of the “dead donor rule” is challenging because it implicates views about a wide range of issues, including whether and when patients are appropriately declared dead, the validity of the doctrine of double effect, and the moral difference between or equivalence of active euthanasia and withdrawal of life-sustaining treatment. The DDR will be defined here as the prohibition against removal of organs necessary for the life of the patient—that is, the prohibition of intentionally ending the life of a patient through organ removal. At a minimum, it is difficult not to see the DDR as grounded in a set of laws, norms, values, and practices that are firmly entrenched and have a great deal of philosophical, religious, and legal support. Obviously, the primary argument against the DDR is that it is highly desirable that we continue to procure organs for transplantation, combined with the belief that those from whom we often and possibly typically procure organs are not “really” dead. If donors are not really dead, then we are left with a dilemma: either we abandon organ procurement, or we abandon the DDR. Such a move should be taken only if the way we currently delineate the dead (those from whom it is acceptable to remove organs) cannot be maintained or defended. I will suggest that this is not the case.